Studi Literatur: Efektivitas Dan Keamanan Penerapan Desinfektan Secara Spraying Untuk Pencegahan Penularan Virus Corona (MERS, SARS, Dan SARS-COV-2) - Fresensi Anggraini Date Meze; Maxs U.E Sanam; Tri Utami (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
Corona Virus is a zoonotic virus (transmitted form animal to human), which is cause disease from light to severe. There are two kind corona virus known in common that could be weight symptoms like Middle East Respiratory Syndrome (MERS-CoV) and Severe Acute Respiratory Syndrome (SARS-CoV). The purpose of compiling this literature study is to identify what kind of spraying disinfectant for prevent spreading, mechanism and safety, effectiveness/ impact spraying disinfectant about corona virus spreading. This literature study was obtained through searching and collecting from various reference sources using the Mendeley and Google Scholar applications. it was found that the type of spraying disinfectant that used to prevent coronavirus, include them were bleach solution (natrium hypochlorite), alcohol,povidone iodine, hydrogen peroxide. The mechanism of action of spraying disinfectants such as bleach solution (sodium hypochlorite) is to oxidize peptide bonds in cell membranes and denature proteins; alcohol disinfectants work by lysing the viral envelope; povidone iodine works by penetrating viral cell walls, oxidizing materials and dominating cells; hydrogen peroxide works by inhibiting the replication process, causing the death of the virus. Spraying disinfectants are quite effective in preventing transmission of the corona virus such as povidone iodine which is able to reduce virus titers and hydrogen peroxide which is able to inactivate the virus within 1 minute, but disinfectants sprayed in the environment or outdoors are not effective enough because they can be inactivated by dust and debris.